The Influence of Savings and Deposits on The Credit Position of Village Kredit Institutions (LPD) in Gianyar District During The COVID-19 Pandemic - KUSUMA, Gusti Ngurah Putu Angga; MARTIN, I Made Verry; DARMA, I Ketut (Journal of Tourism Economics and Policy, 2023)
The background of this research is to analyze the influence of savings and deposits on the credit position of LPDs in Gianyar District during the COVID-19 pandemic. The data used in this research is quantitative data, which includes the value of savings, deposits, and credit. Research on the Effect of Savings and Deposits on the Credit Position of Village Credit Institutions (LPD) in Gianyar District During the Covid-19 Pandemic. The object of this research is community savings funds (Savings and Deposits) and (Credit) in LPDs in Gianyar District.  The data analysis technique used is Panel Data Regression Analysis, where the independent variables are Savings and Deposits while the dependent variable is Credit. The test results explain Savings and deposits, together with all the independent variables used in the research, can influence the credit position of Village Credit Institutions (LPD) in Gianyar District during the COVID-19 pandemic.  Savings have had a significant effect on the credit position of Village Credit Institutions (LPD) in Gianyar District during the COVID-19 pandemic. Deposits have had a significant effect on the credit position of Village Credit Institutions (LPD) in Gianyar District during the COVID-19 pandemic.